Digital watermarking in A udio signals for covert data Transmission (Journal of the College of Basic Education, 2023)
With increasing the usage of digital multimedia, the protection of intellectual property rights problem has become a very important issue. Everyday, thousands of multimedia files are being uploaded and downloaded. Therefore, multimedia copyrights become an important issue to protect the intellectual property for the authors of these files. So, this research presents an audio watermarking method that embed a watermark bit in the four LSB layers of audio signal; the algorithm is applied to a stereo audio signal. Embedding watermark in these layers of a sample is equivalent to adding a noise to original signal. The noise level due to embedding watermark is significantly reduced if it is compared with standard LSB watermarking scheme and the quality of watermarked signals is also improved. So, the idea of a proposed algorithm is to obtain a minimal error due to embedding a watermark in an audio signal. Robustness under some attacks is also performed such as resampling and adding noise.